SITUS BESOLE: SISA-SISA PINTU GERBANG DARI MASA KADIRI - Kuswanto Kuswanto (Berkala Arkeologi, 2009)
Besole is a site wher remants of a brick gateway were found. This site is assumed to be dated from Kadiri Kingdom period (1041 AD – 1222 AD), though it exists in Blitar district. The gateway is an important element in a building complex or a city. The existence of a gateway can show the complexity of the neighbourhood. This article will discuss about the invention, rescue, and interpretation of the remmants in Besole as a contribution to reconstruct the nation civilization history.